ANALYSIS OF SIAMESE ORANGE FARMER’S HOUSEHOLD INCOME IN KUOK DISTRICT OF KAMPAR REGENCY - Fauzi Ardiansyah; Eliza Eliza; Evy Maharani (Indonesian Journal of Agricultural Economics, 2021)
The study aims to analyze the household income of citrus farmers in Kuok Subdistrict, Kampar Regency based on agricultural income and non-farm income and analyze factors that affect the household income of siamese farmers. The research was conducted from March 2019 to April 2020 in Kuok District, Kampar Regency. The study was conducted by direct interview technique to siamese orange farmers, the number of respondents to 72 siamese orange farming households was taken accidentally from two villages namely Kuok Village and Four Halls. The data used is primary data and secondary data obtained from kuok subdistrict office, Kuok village office and four halls. The data is analyzed descriptively quantitaif and presented in table form. The results showed that based on the coefficient value of factors that affect the household income of siamese orange farmers, land area factors and total costs have a positive influence on the increase in household income of siamese orange farmers derived from farming. Income from farming contributes very much in household income which is 93.24 percent while outside the farm only contributes 6.76 percent. Income from siamese citrus farming contributes more than the oil palm farm. The average household income of siamese orange farmers is Rp. 6,392,359.77 per month. The value of R / C ratio obtained, siamese orange farming and palm oil is very feasible to develop because it has a R / C ratio above 1. Siamese citrus farming has an R/C ratio of 2.44 and palm oil farming has an R/C ratio of 3.31.